(untitled) (Journal of Computational Mathematics, 1988)
This paper discusses the sensitivity of semisimple multiple eigenvalues and corresponding invariant subspaces of a complex (or real) n× n matrix analytically dependent on several parameters. Some results of this paper may be useful for investigating robust multiple eigenvalue assignment in control system design.